Situational Determinants of Supervisor Attributions and Behavior - McFillen, James M.; New, J. Randolph (Academy of Management Journal, 1979)
Forty subjects, randomly assigned to a supervisory role in either a reward power only or penalty power only condition, supervised two successful subordinates, one closely and one generally, and two unsuccessful subordinates, one closely and one generally. Only subordinate performance was found to affect consistently the supervisor's perceptions of subordinate performance and the allocation of incentives and subsequent supervision.